CAPITAL STRUCTURE AND EARNINGS VOLATILITY AND CASH FLOW EVIDENCE FROM ASEAN COMMERCIAL BANKS - Nicholas Felixsky; Rita Juliana (Sampoerna University, 2025)
This research aims to observe the impact of capital structure on earnings volatility and cash flow of commercial banking companies in ASEAN country. This research uses yearly secondary data of company’s financial report from 2015-2024 period. The variables studied in this research are aspects of the capital structure of banking companies, included Debt to Equity Ratio, Debt to Assets Ratio, and Deposits to Equity ratio, and as well as Earnings Volatility, Operating Cash Flow, and Operating Cash Flow Volatility. The data was analyzed using panel data method, specifically using Driscoll Kraay robust standard error with Fixed Effect Model. The results of this research showed that Debt to Assets Ratio, Debt to Equity Ratio, and Deposits to Equity Ratio each had a significant impact on Earnings Volatility, Operating Cash Flow, and Operating Cash Flow Volatility.